Reviving Adat Law: The Middle Way between Tradition and Modernity in Ecology - Natsir, Muhammad; Iqbal, Muhammad (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2024)
The revitalization of customary law is an effort to integrate traditional values with modernity in sustainable environmental management. Customary law plays a crucial role in maintaining ecosystem balance and ensuring the sustainability of natural resources through principles rooted in local wisdom. However, exploitative economic development and growth-oriented policies often overlook its significance. This study analyzes the challenges, causes, and solutions in revitalizing customary law to create synergy between tradition and modernity. A qualitative approach is employed through in-depth interviews, field observations, and focus group discussions (FGDs) to assess its effectiveness in environmental conservation. The findings indicate that the revitalization of customary law can enhance the effectiveness of natural resource management, strengthen the rights of Indigenous communities, and mitigate conflicts between economic and environmental interests. Integrating customary law into national and international policies, raising public awareness, and fostering cross-sector collaboration are strategic steps to optimize its role in maintaining ecological and economic balance.